2021
DOI: 10.1111/ijcp.14772
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers' sleep quality after COVID‐19 infection: A cross‐sectional study

Abstract: Introduction The COVID‐19 pandemic not only affected physical health but also caused high levels of mental health problems including sleep disturbances, depression and post‐traumatic stress symptoms. The aim of this study was to examine the sleep parameters of healthcare workers before COVID‐19 infection and after recovery. Materials and Methods Healthcare workers who were infected with COVID‐19 and whose treatment was completed at least 30 days ago were included in the study. A web‐based cross‐sectional surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 25 publications
1
21
1
2
Order By: Relevance
“…Similarly, this cohort with post-COVID-19 showed limited impact on sleep disturbance, which has been reported in prior studies. 14,79 In addition to cardiopulmonary sequela, post-COVID-19 may impact a variety of neurosensory functions, such as loss of smell or taste. 39,66,123 The shared symptomology between post-COVID-19 and FMS may conversely suggest the potential for elevated sensory sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this cohort with post-COVID-19 showed limited impact on sleep disturbance, which has been reported in prior studies. 14,79 In addition to cardiopulmonary sequela, post-COVID-19 may impact a variety of neurosensory functions, such as loss of smell or taste. 39,66,123 The shared symptomology between post-COVID-19 and FMS may conversely suggest the potential for elevated sensory sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also presented in two studies that evaluated self-reported sleep disturbances in HCW. Compared with before the initial infection, overall sleep quality and multiple sleep parameters such as latency, duration, efficiency, use of sleep medication and daytime dysfunction were found to be significantly altered in HCW at two months after the initial COVID-19 infection [ 131 ]. Similarly, Gaber et al [ 132 ] observed that almost half of HCW exhibited at least one symptom several months after the initial infection, with similar rates of sleep (49%) and mood (44%) disturbances.…”
Section: Quantitative and Qualitative Alterations Of Sleep In Acute A...mentioning
confidence: 99%
“…The beforementioned studies described self-reported sleep disturbances, evaluated through questionnaires and interviews [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 131 , 132 ], and only one study reported PSQI values [ 131 ].…”
Section: Quantitative and Qualitative Alterations Of Sleep In Acute A...mentioning
confidence: 99%
“… 7 Sleep quality was found to be significantly decreased even after recovery of COVID-19 in those infected individuals. 24 It was also documented that preexisting EDS was significantly associated with the risk of mortality and hospitalization in patients infected by COVID-19. 25 Thus, there could be a close link between COVID-19 and EDS, albeit that the underlying mechanism remained unclear.…”
Section: Discussionmentioning
confidence: 98%